PENGARUH PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR MERK HONDA TYPE MATIC (STUDI KASUS PADA MAHASISWA STIE NASIONAL BANJARMASIN) - - Mailiana; - Masrifani; Ni Nyoman Suarniki (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2019)
Abstract, This study aims to find out and analyze the factors that influence consumer behavior towards purchasing decisions of automatic Honda motorcycles. The population in this study were students of STIE Nasional Banjarmasin. The sample of this study was 60 people from the management department of class 2014. The method used to conduct this research is descriptive method. The analytical tool used in this study is multiple linear regression analysis Partial test results (T test) of this study are 1). Cultural factors have a significant effect on purchasing decisions of automatic Honda motorcycles. 2). Social factors have a significant effect on purchasing decisions of automatic Honda motorcycles. 3). Personal factors have a significant effect on purchasing decisions of automatic Honda motorcycles. 4). Psychological factors have a significant effect on purchasing decisions of automatic Honda motorcycles. While the Simultaneous test results (F test) of this study are cultural factors, social factors, personal factors and psychological factors have a significant effect on the purchase decision of automatic Honda motorcycles. The conclusion of the description described can be concluded that the results of the study show that the Cultural Factor variable has the greatest influence so that it is the most dominant variable in purchasing decisions.